Impact of Political and Cultural Factors on Online Education in Africa: the Strategies to Build Capabilities - Singh, Satyendra; Lewa, Peter M. (Organizations and Markets in Emerging Economies, 2014)
Recently the concept of online education has received considerable attention worldwide; however, its low success rate in Africa warrants further investigation. The purpose of this study is to examine the impact of political and cultural factors on online education. For the purpose of the study, the political factor constitutes government support, technological infrastructure and trained instructors, whereas the cultural factor focuses on gender bias, culture bias and language barrier of learners. Drawing on the theory of source-position-performance, we argue that source (i.e., online education) should be promoted in rural areas as usages of mobile technologies and cellphones are more than computers, and that online education leads to competitive advantage. Finally, we propose a couple of strategies to build capability.